Measuring Student’s Perception Towards the Implementation of Moodle-Based E-Learning Platform in ELT: A Rasch Model Measurement - PILU, Reski; SUHRAH, Suhrah (Politeknik Negeri Ujung Pandang, 2025)
The wide-ranging and provision of high-end technology have brought a significant impact on the world of education. Teacher and student are expected to collaborate effectively in learning process using technology. This paper reveals the investigation on student’s perception towards the implementation of Moodle-based e-learning in ELT as well as some problems encountered by the users (learners) in utilizing the platform. A mix method approach was employed using online survey and interview. Three classes consisting 62 students who have experienced a Moodle-based e-learning were engaged both in the survey and interview. The data obtained from the online survey was analyzed using a RASCH measurement analysis with IRT (Item Response Theory) approach. The result shows a positive trend on student’s perceived usefulness (PU), ease of use (EoU), behavioral intention (BoI) towards the implementation of the platform. This article also provides several suggestions for further research and development within the area of Moodle-based e-learning platform.